Fenomena Demotivasi Belajar Bahasa Arab di Indonesia - Ramli, Ramli (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
Arabic Language is the oldest foreign language (second language) known and studied by the Indonesian people. Arabic was known and studied in Indonesia long before other foreign languages ​​such as English, German, and Mandarin. In the 1980s, Arabic was the favorite language for students in Indonesia. However, over time, the love and enthusiasm for learning Arabic in Indonesia has decreased. This phenomenon is called the "Phenomenon of Devotion to Learn Arabic". The phenomenon of Demotivation to Learn Arabic in Indonesia can be seen from a number of research results, including the results of a survey conducted in Malang and the results of research conducted in Palang Karaya, Kalimantan. There are a number of factors that influence demotivation to learn Arabic in Indonesia, namely teacher factors which include the low quality of Arabic teachers, environmental factors, and internal factors of students. And to be able to overcome these problems, it is necessary to improve the quality of Arabic teachers, both in terms of Arabic language skills and mastery of teaching methods, create a conducive and effective Arabic language environment and raise awareness of the importance of Arabic in the current digital era